What performance-related variables best differentiate between eliminated and qualified teams for the knockout phase of UEFA Champions League? - Almeida, C. R. (Sport Performance & Science Reports, 2018)
The UEFA Champions League is the most prestigious football club competition worldwide (1). Reaching the knockout phase is paramount for participant clubs to warrant more revenues and international reputation. Although performance pro les vary among teams (2, 3), match events as total attempts, shots on target and passing accuracy have been previously associated with success in this tournament (1, 3, 4). However, since other performance-related variables (e.g., ball possession or yellow cards) displayed contradictory results (3, 4), further research is required to clarify the contemporary trends of successful teams' performance in elite football (5, 6). Aim: This study aimed to identify the team performance variables of total attempts, shots on target, goalkeeper's (Gk) saves, ball possession, completed passes, passing accuracy, distance covered, balls recovered, fouls committed, yellow and red cards that best differentiate between eliminated and qualified teams for the knockout phase of 2017/2018 Champions League.